2017
DOI: 10.5114/pg.2017.72105
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and duration of treatment with propranolol in children with cyclic vomiting syndrome in southern Iran

Abstract: IntroductionCyclic vomiting syndrome is a functional disorder characterised by repeated episodes of nausea and vomiting with symptom-free intervals between the attacks. Cyclic vomiting syndrome is a migraine equivalent; therefore, anti-migraine medications are effective for cyclic vomiting syndrome prophylaxis, but duration of treatment is not clear.AimTo determine the efficacy and duration of drug therapy in cyclic vomiting syndrome.Material and methodsThis study was conducted on 206 cases of cyclic vomiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…4 Timely diagnosis and treatment with propranolol have been suggested in several studies. [15][16][17] All of the 504 children had emesis and vomiting, which consistent with other studies in the field, is characteristic of the disease. 18,19 The results indicated that the average incidence age was 52 months (4.3 years) and the average age at diagnosis was 69.9 months (5.8 years).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…4 Timely diagnosis and treatment with propranolol have been suggested in several studies. [15][16][17] All of the 504 children had emesis and vomiting, which consistent with other studies in the field, is characteristic of the disease. 18,19 The results indicated that the average incidence age was 52 months (4.3 years) and the average age at diagnosis was 69.9 months (5.8 years).…”
Section: Discussionsupporting
confidence: 85%
“…15,16 Meanwhile, efficiency rate, lack of disease symptoms relapse after stopping treatment, and treatment duration (especially in children) are among important and unclear problems in previous reports and studies, which are the focus of the present study. Duration of the treatment period in children with CVS can also http://mejdd.org be useful in…”
mentioning
confidence: 97%
“…As a result, not only their quality of life is not improved but also by discontinuation of prophylaxis, the risk of the transforming the episodic migraine to the chronic type increases, and subsequently, other major complications such as cardiovascular incidents increase. [14] The objective of this research was to evaluate the use of VFL as an alternative to the combination of nortriptyline and propranolol, assuming that it has fewer side effects with similar or greater effects on the frequency or severity of headaches, and thus, it is more tolerable in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Its efficacy was evaluated in 311 patients across 2 extensive prospective studies and 1 retrospective study. 22,26,27 Haghighat et al compared the effectiveness of propranolol with that of amitriptyline, and observed that 89% of patients treated with propranolol demonstrated a "good response" without side effects, in contrast to a 56% overall response rate in patients treated with amitriptyline. 22 Furthermore, no side effects were reported among the propranolol-treated patients, unlike the amitriptyline group.…”
Section: Treatment Of Cvs Comparing Standard Therapy Withmentioning
confidence: 99%